2021
DOI: 10.1007/s11606-020-06572-w
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Scoring Tool to Predict Medical Intensive Care Unit Readmissions Based on Both Patient and Process Factors

Abstract: BACKGROUND: Although many predictive models have been developed to risk assess medical intensive care unit (MICU) readmissions, they tend to be cumbersome with complex calculations that are not efficient for a clinician planning a MICU discharge. OBJECTIVE: To develop a simple scoring tool that comprehensively takes into account not only patient factors but also system and process factors in a single model to predict MICU readmissions. DESIGN: Retrospective chart review. PARTICIPANTS: We included all patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The most common modeling technique was logistic regression. Twenty-three studies evaluated at least one logistic regression model (15–18, 23, 24, 26–29, 31–40, 42, 43, 46). Other model techniques included recurrent neural networks (22, 30), gradient boosting machines (14, 25), and artificial neural networks (23).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common modeling technique was logistic regression. Twenty-three studies evaluated at least one logistic regression model (15–18, 23, 24, 26–29, 31–40, 42, 43, 46). Other model techniques included recurrent neural networks (22, 30), gradient boosting machines (14, 25), and artificial neural networks (23).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-three studies were included in the final analysis, as summarized in Supplemental Table 1 (http://links.lww.com/CCX/B130) (14–46). Twenty-five studies recruited patients from a single center; eight studies (14–19, 29, 42) reported results from two or more centers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation